The Approach and Device for Water Radon Measurement with Overflowing Electret - ZHANG Hui1;DENG Jun2;XU Le-chang1;LI Xian-jie1 (Journal of Isotopes, 2016)
To solve the difficulties in “original” radon concentration measuring, this paper proposed an overflow type electret radon concentration measurement method and device. A 4 L jar was applied as ionization chamber and E-perm electret was applied as radon detector. When the steady radon contaminated water flowed through the ionization chamber, water radon was released with the nitrogen aerating disturbance. The average radon concentration was detected by the E-perm electret. Furthermore, RAD7-H2O kit was used to measure the radon concentration for comparison. The results showed that different methods had well consistency with the water radon concentration in the range of 4 to 97 Bq/L.